Robert Capa: In Love and War - Makepeace, Anne (United States, 2003)
Heralded as the pre-eminent documentarian of the 20th century, Robert Capa (1913-1954) photographed five epic conflicts on three continents, all in the 40 short years of his life. This is a compelling insight into the life and loves of the iconic war photographer. Celebrated as the "Greatest War Photographer in the World," the Hungarian-born Robert Capa achieved fame with the Spanish Civil War of 1936. It was during this conflict that Capa produced heartbreaking image of Falling Soldier, capturing the death of a Spanish freedom fighter at the moment of the bullet's impact. Capa went on to photograph several of the major battles of WWII, including D-day. His brilliance with the camera transformed Capa into an international celebrity, bringing him in close contact with several other notables, among them actress Ingrid Bergman, with whom he had a brief romance. Bergman's daughter Isabella Rosellini is among those interviewed in this documentary. He died stepping on a land mine during his coverage of the French-Indochina war of the early 1950s.
Duration: 01:32:00
Keywords: Documentary films